THE EFFECTS OF GREEN PERCEIVED VALUE ON GREEN CUSTOMER LOYALTY THROUGH GREEN SATISFACTION AND GREEN TRUST (A STUDY OF THE USERS OF AVOSKIN SKINCARE PRODUCT IN MALANG CITY) - Nafilah Fauziyah Mahartin; Mugiono; Sudjatno (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The purpose of this research is to assess the effects of green perceived value, green satisfaction, and green trust on green loyalty. The population of this quantitative explanatory research is the users of Avoskin, a skincare brand, in Malang City. Using purposive sampling technique, 214 people were selected as the respondents. The research data was harvested via Likert-scaled questionnaires and documentations and was analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS).This study finds that green perceived product significantly influences green loyalty, green satisfaction, and green trust. Further, green satisfaction and green trust were found to partially mediate the relationship between green perceived value and green loyalty. Based on these findings, Avoskin is suggested to innovate and increase the benefit values for its consumers as these efforts improve customer satisfaction and trust, which finally lead to higher loyalty to the brand.